2020
DOI: 10.1111/gcb.15059
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting intensifying disturbance effects on coral reefs

Abstract: Anticipating future changes of an ecosystem's dynamics requires knowledge of how its key communities respond to current environmental regimes. The Great Barrier Reef (GBR) is under threat, with rapid changes of its reef-building hard coral (HC) community structure already evident across broad spatial scales. While several underlying relationships between HC and multiple disturbances have been documented, responses of other benthic communities to disturbances are not well understood. Here we used statistical mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 75 publications
0
45
0
Order By: Relevance
“…Data analysis on abundance (percent cover) of benthic groups within the Karimunjawa National Park were performed using the R software (R Core Team 2016), following a methodology developed by Vercelloni et al [53]. Benthic groups were aggregated into Hard coral, Soft coral, Algae, Sponge and Sediment by summing different sub-groups to produce group relative abundances (Appendix A, Table A2).…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Data analysis on abundance (percent cover) of benthic groups within the Karimunjawa National Park were performed using the R software (R Core Team 2016), following a methodology developed by Vercelloni et al [53]. Benthic groups were aggregated into Hard coral, Soft coral, Algae, Sponge and Sediment by summing different sub-groups to produce group relative abundances (Appendix A, Table A2).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Quadrats were grouped into 100 m sub-transects, a) in order to exclude any data where transect line deviated, so that the exact same section of reef (to within 5 m, the GPS error range) could be directly compared between years, and b) so that data analysis took place at an appropriate ecological scale [53]. Sub-transects were generated using hierarchical clustering based on Euclidean distance between geo-located quadrats within transects [53]. We retained sub-transects composed of a minimum of three images per surveyed year and repeated in 2014 and 2018.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…For example assessment of symbiont community (Suggett, Warner, & Leggat, 2017) and cellular memory (Brown, Dunne, Edwards, Sweet, & Phongsuwan, 2015) in the coral holobiont during and after thermal stress, to test for shifting physiological status that may ameliorate or exacerbate coral bleaching. Thus, physiotype tracking – or multivariate physiological and molecular time series data – provide the capacity for identification of the cellular mechanisms that contribute to resilience, acclimatization, and/or resistance that can allow for better predictions of coral ecological responses to intensifying climate change and other regional disturbances (Vercelloni et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, coral reefs are negatively affected by pressures such as climate change, which have caused a substantial decline in hard coral abundance (Ainsworth et al, 2016;De'ath et al, 2012;GBRMPA, 2014a,b). In addition, monitoring the GBR is especially challenging because it extends over 346, 000 km 2 and traditional marine surveys are expensive (Nichols & Williams, 2006;Nygård et al, 2016;Roelfsema & Phinn, 2010;Vercelloni et al, 2020). To address these issues, Peterson et al (2020) demonstrated how image-based coral cover data elicited from citizens can be combined with other professional data sources to improve the spatio-temporal data coverage in the GBR and increase the information gained to inform management.…”
Section: Origins Of Coral Reef Imagesmentioning
confidence: 99%